Functional traits that moderate tropical tree recruitment during post‐windstorm secondary succession. (5th February 2020) - Lai, Hao Ran; Chong, Kwek Yan; Yee, Alex Thiam Koon; Tan, Hugh Tiang Wah; van Breugel, Michiel
Abstract: Understanding how functional traits moderate species' demographic responses along environmental gradients is a core pursuit in ecology, often to predict how species abundances will respond to a rapidly changing environment. The latter necessitates species demography, or at least abundance, to be modelled directly as a response; yet, most studies till date use abundance indirectly to calculate and then correlate community‐aggregated trait indices to environmental variables, rendering the prediction of species demographic responses along environmental gradients unfeasible. Using a hierarchical Bayesian approach that stems from joint species distribution modelling, we modelled the recruitments of 53 woody plant species along windstorm‐generated environmental gradients from twenty‐eight 100‐m 2 tropical secondary forest plots censused over 5 years in Singapore, and then examined whether environmental responses across species can be explained and generalized by functional traits. We found that species recruitment along the light‐availability gradient was moderated by wood density, in that low wood‐density species responded more positively to elevated light conditions by being more responsive in height growth. Seed mass moderated species recruitment along the leaf litter depth gradient, such that large‐seeded species with greater energy reserves recruited more in sites with thicker leaf litter depths than small‐seeded species. Shorter‐ and taller‐statured species recruited more in historically short‐ and tall‐canopied forest sites, respectively, indicating an influence from surrounding parent trees and the importance of considering dispersal limitation in successional studies. Leaf economic traits (specific leaf area, leaf dry‐matter content and lamina thickness) did not moderate recruitment responses across environments, suggesting a weak role of leaf traits during the earlier life stages or their high plasticity. Synthesis . Wood density, seed mass and adult stature are the main traits that moderate sapling recruitment in our wind‐generated forest gaps. The roles of multiple traits in moderating the shared environmental responses across species may be crucial in the maintenance of coexistence and diversity through niche partitioning. Most importantly, we estimated the strength and direction of trait effects on species responses to environmental changes during succession. These are potentially generalizable results that can directly predict the demographic responses of any species—given its traits—to environmental changes. Abstract : In a tropical lowland rainforest in Singapore, the recruitment of 53 woody plant species along windstorm‐generated gradients of canopy openness and leaf litter depth were moderated by wood density and seed dry mass, respectively, while adult stature/maximum height moderated species recruitment in young or old secondary forest type. Second‐Language Abstract (Mandarin): 群落生态学正积极探讨功能性状（functional traits）如何影响物种在不同环境条件下的群落反应，以便预测物种多度将如何反应于迅速的全球变化。这类研究的反应性变数必须是群落统计或种多度，但目前大部分研究都只用种多度来计算群落层次的功能性状指数，然后将群落功能性状指数作为反应性变数。 在新加坡一片遭暴风侵袭的热带次生雨林内，我们设置了28个样区（各100方米）并进行了五年的动态观察。我们采用了建立于联合种群分布模型（joint species distribution models）的多层贝叶斯方法（hierarchical Bayesian approach）来估计53种木本植物在环境变化下的新增（recruitment），同时探索植物功能性状能否解释和概括不同物种之间对环境的新增反应。 本研究发现拥有较低木材密度（wood density）的物种对光度有较强的正反应，于是在开阔的林冠下有较多新增。拥有较轻种子干质量（seed dry mass）的物种随着落叶层增厚而减少新增，或许是因为轻种子拥有较少的能量储备。拥有较矮最大树高（maximum height）的物种在低冠林里新增较多，而拥有较高最大树高的物种则在高冠林内新增较多——这显示新增树苗的物种反映着周遭母树的物种，也表示种子扩散限制（dispersal limitation）在次生演替上的重要性。与叶子相关的功能性状对物种在不同环境下的新增并无影响，或许是由于叶功能形状在早期的生命周期并不重要，又或是因为叶性状较为弹塑。 总结： 在遭风暴改变的森林环境之下，木材密度、种子干质量和最大树高影响物种的新增。多个功能性状对各物种环境反应的共同影响，可以是多物种通过区分生态位以达成共存的机制。更重要的是，这些植物功能性状概括了物种之间对环境不同的反应，以让我们能够凭功能性状来预测某物种在未来更多变的气候下对环境变迁的反应。